MR Imaging in Human Rabies - Laothamatas, Jiraporn; Hemachudha, Thiravat; Mitrabhakdi, Erawady; Wannakrairot, Pongsak; Tulayadaechanont, Supoch (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Whether human rabies of different forms, encephalitic (furious) and paralytic (dumb), share similar MR imaging patterns is unknown. We assessed the diagnostic value of MR imaging in both forms of the disease and compared the clinical and neuroimaging findings.METHODS: Three patients with paralytic and two with encephalitic rabies were examined during preserved or deteriorated levels of consciousness. Six MR examinations of the brain, three of the spinal cord, and one of the brachial plexus were performed with a 1.5-T superconducting magnet.RESULTS: No difference was noted between the MR findings in both clinical forms of human rabies. Nonenhancing, ill-defined, mild hyperintensity changes in the brain stem, hippocampi, hypothalami, deep and subcortical white matter, and deep and cortical gray matter were demonstrated on T2-weighted images in the noncomatose patients with rabies. Enhancement along the brachial plexus of the bitten arm was noted in one patient with encephalitic rabies who at that time had only local neuropathic pain symptoms. Enhancement with gadolinium-based contrast material was seen at the hypothalami, brain stem nuclei, spinal cord gray matter, and intradural cervical nerve roots only when the patients became comatose.CONCLUSION: Both forms of human rabies share a similar MR imaging pattern. Such pattern and the lack of enhancement in a noncomatose patient with suspected encephalitis may differentiate rabies from other viral encephalitides.